2020
DOI: 10.1002/htj.21690
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of unsteady natural convection flow of a Casson viscoplastic fluid in a square enclosure utilizing a MAC algorithm

Abstract: Non-Newtonian fluids are increasingly being deployed in energy systems and materials processing. Motivated by these developments, in the current study, a numerical simulation is performed on twodimensional, unsteady buoyancy-driven flow in a square cavity filled with non-Newtonian fluid (Casson liquid). The enclosure geometry features vertical isothermal walls (with one at higher temperature than the other) and thermally insulated horizontal walls. The conservation equations for mass, momentum, and energy are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…4 and are the cavity's inclination angle v = 0 in case (I) and v ¼ p 4 in case (II). The average heat transfer rate is computed for four combinations of ternary nanofluids: Source: Wan et al, 2001;De Vahl Davis, 1983;Devi et al, 2020 In case (I), in the absence of the magnetic field parameter (Ha = 0), the primary and secondary circulation cells are formed horizontally within the cavity. The primary circulation cells are densely formed at the bottom of the cavity, while some secondary cells are formed in the upper part of the cavity, as portrayed in Figure 4(a) (I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and are the cavity's inclination angle v = 0 in case (I) and v ¼ p 4 in case (II). The average heat transfer rate is computed for four combinations of ternary nanofluids: Source: Wan et al, 2001;De Vahl Davis, 1983;Devi et al, 2020 In case (I), in the absence of the magnetic field parameter (Ha = 0), the primary and secondary circulation cells are formed horizontally within the cavity. The primary circulation cells are densely formed at the bottom of the cavity, while some secondary cells are formed in the upper part of the cavity, as portrayed in Figure 4(a) (I).…”
Section: Resultsmentioning
confidence: 99%
“…We modified the current flow model to the Wan et al (2001) model, and then the accuracy was checked by streamlines, isotherms and U and V velocity profiles, which showed good agreement. Further, the obtained average Nusselt number results are numerically compared with Wan et al (2001), De Vahl Davis (1983) and Devi et al (2020) analysis, as shown in Table 5. It shows good accuracy with their results.…”
Section: Marker and Cell Procedures And Validationmentioning
confidence: 99%
“…Based on the discussed assumptions, the dimensional coupled partial differential equations are (the conservation of mass, momentum, and thermal transport equations) expressed in the Cartesian form as follows 11,35‐38 u x + v y = 0 , ρ u t + u u x + v u y = p x + μ + κ 2 u x 2 + 2 u y 2 + κ N y , ρ v t + u v x + v v y = p y + μ + κ 2 v x 2 + 2 v y 2 κ N x σ ρ B 0 2 v + g β T T c , ρ j N t + u N x + v N y = γ 2 N ∂<...>…”
Section: Problem Formulation and Governing Equationsmentioning
confidence: 99%
“…Aneeta Razaq et al 13 discussed Cattaneo-Christov heat flux and thermal transport processes. Khan et al 14 In this article, the influence of the diffusion-thermo and thermo-diffusion on double diffusive free convection in a square chamber filled with fluids, non-Darcy porous medium are investigated the resulting nondimensional partial differential equation of the boundary value problem is solved by the Marker and Cell (MAC) method [16][17][18] and the finite difference forward and backward scheme along a staggered grid system. The Dufour effect is the energy flow caused by concentration gradients, while the Soret effect is the mass flux caused by temperature gradients.…”
Section: Introductionmentioning
confidence: 99%